Skip to main content

Do you know the sum of 1 to infinity is -1/12๐Ÿค“๐Ÿค“๐Ÿ˜ฎ๐Ÿ˜ฎ๐Ÿ˜ฎ๐Ÿค”๐Ÿค”๐Ÿคฏ

           Have you ever imagined 

What will be the sum of               1+2+3+4+5+.........+∞

Do you know the formula 
n(n+1)/2 for finding sum of first 'n' natural number. 
Example: if we to find sum of  first 20 natural numbers then,we apply the above formula
n(n+1/)2 
20(20+1)/2
(20*21)/2
=210

But in case of infinity
We don't know what will have to place in place of 'n' in formula "n(n+1)/2"

But a great Indian Mathematician Mr. Srinivas Ramanujan solves this problem, and  prove that sum of 1 to  ∞ is = -1/12
Then we know the equation 1+2+3+4+5+.........+∞ = -1/12 as Ramanujan Summation.

Let's see the proof

Let
A = 1-1+1-1+1-1+1-1................∞
       We expect that after solving the equation we get A= 0
But our supposition is wrong, let's see why๐Ÿ‘‡๐Ÿ‘‡๐Ÿ‘‡๐Ÿ‘‡

1-A = 1-(1-1+1-1+1-1+1-1................∞)
       After opening the bracket the symbols got changed ๐Ÿ‘‡๐Ÿ‘‡๐Ÿ‘‡๐Ÿ‘‡๐Ÿ‘‡
1-A = 1-1+1-1+1-1+1-1+1.................∞
1-A = A
1=A+A
1=2A
A= 1/2
        It is amazing to get that 
1-1+1-1+1-1+1-1.........∞ = 1/2

Let's do an another equation
B= 1-2+3-4+5-6+7...............∞
A-B = (1-1+1-1+1-1+1-1+.....)-(1-2+3-4+5-6+7.........)
      After opening the bracket, all symbols  in brackets get changed 
A-B = (1-1+1-1+1-1+1-1+.....)-1+2-3+4-5+6-7.............
     Let's do a little shuffling(rearranging)
that is how, I did reshuffling

A-B = (1-1)+ (-1+2)+(1-3)+(-1+4)+(1-5)+(-1+6)+(1-7).......

A-B = 0+1-2+3-4+5-6+7..........
A-B = 1-2+3-4+5-6+7............ It is same as B
A-B = B
A= B+B
A = 2B
1/2 = 2B.           (A = 1/2) proved above
B = 1/4
This means 
1-2+3-4+5-6+7.......... = 1/4
Is this equations getting amazing, isn't it๐Ÿค“๐Ÿค“๐Ÿค“๐Ÿค“๐Ÿค“๐Ÿค“๐Ÿค“๐Ÿค“๐Ÿคจ๐Ÿ˜ฎ๐Ÿ˜ฎ๐Ÿ˜ฎ๐Ÿ˜ฎ

Let's do the last step
Let
C = 1+2+3+4+5+6+7............
B-C = (1-2+3-4+5-6+7.........) - (1+2+3+4+5+6+7+...............)

      All symbols in brackets got changed ๐Ÿ‘‡๐Ÿ‘‡๐Ÿ‘‡๐Ÿ‘‡๐Ÿ‘‡๐Ÿ‘‡๐Ÿ‘‡๐Ÿ‘‡๐Ÿ‘‡๐Ÿ‘‡๐Ÿ‘‡๐Ÿ‘‡

B-C = (1-2+3-4+5-6+7........)-1-2-3-4-5-6-7-.............

      Let's do a little bit shuffling again

B-C = (1-1)+(-2-2)+(3-3)+(-4-4)+(5-5)+(-6-6)+(7-7)+............

B-C = 0+(-4)+0+(-8)+0+(-12)+.........
B-C = -4-8-12....................

   Taking -4 as common

B-C = -4(1+2+3+4+5..............)
B-C = -4(C)
B-C = -4C
B = -4C+C
B = -3C
1/4 = -3C.      (B = 1/4) proved above
C = -1/12

This means

1+2+3+4+5+6+7.........∞ = -1/12
        
     Do you think, this is true
It doesn't seems to be true because sum of positive integer gives us a negative integer ,also which is in fraction

This Ramanujan Summation is used in solving many equation of physics
Let's appreciate our Indian legend  Sir 'Srinivas Ramanujan'.



If you want to see my posts related to technology you can Click here

If you want to see my posts related to study you can Click here

If you like my article, comment below and if you want to give me some suggestion, you can give me in comment section ๐Ÿ‘‡๐Ÿ‘‡๐Ÿ‘‡๐Ÿ‘‡๐Ÿ‘‡๐Ÿ‘‡๐Ÿ‘‡๐Ÿ‘‡๐Ÿ‘‡๐Ÿ‘‡๐Ÿ‘‡๐Ÿ‘‡๐Ÿ‘‡๐Ÿ‘‡๐Ÿ‘‡๐Ÿ‘‡๐Ÿ‘‡

Comments

Post a Comment